Lexical Repetitions Functioning as Connectors in Verse Discourses - Ćarkić, Milosav Ż. (Stylistyka, 2006)
The subject of this article are lexical repetitions functioning as connectors, or perfor[1]ming the organizational function, by serving as a means of connecting various poetic elements, giving compactness, expressiveness and multiplicity of meanings to the poetic creation as a whole.